Invasion and ecological impact of the biofouling tube worm Hydroides elegans (Polychaeta: Serpulidae) in Korean coastal waters - Kim, Sang Lyeol; Yu, Ok Hwan (Frontiers in Marine Science, 2025)
Biofouling, the colonization of submerged surfaces by organisms including microorganisms, plants, algae, and animals, involves both natural and artificial environments. The serpulid worm Hydroides elegans, known as an invasive species in global port areas, creates extensive aggregations of calcareous tubes. In 2019, H. elegans was found attached to the research vessel ISABU in Korea, and a phylogenetic analysis was conducted to identify the species and determine its genetic characteristics. Following its detection, mesocosm experiments with plastic panels (PP, PE, PET, and EPS) were undertaken to investigate its recruitment and adaptation processes within new ecosystems. During the 12-week experiment, the biomass of H. elegans increased on all plastic types, significantly contributing to the overall biomass accumulation. This invasive species has replaced the previously prevalent native species Hydroides ezoensis, achieving dominance over other taxonomic groups in biomass. These findings demonstrate the significant ecological disruptions caused by non-indigenous species introduced through maritime activities, highlighting the urgent need for enhanced preventative and monitoring strategies